An Accurate Upper Bound Solution for Plane Strain Extrusion through a Wedge-Shaped Die - Sergei Alexandrov; Yusof Mustafa; Yeong-Maw Hwang; Elena Lyamina (The Scientific World Journal)
An upper bound method for the process of plane strain extrusion through a wedge-shaped die is derived. A technique for constructing a kinematically admissible velocity field satisfying the exact asymptotic singular behavior of real velocity fields in the vicinity of maximum friction surfaces (the friction stress at sliding is equal to the shear yield stress on such surfaces) is described. Two specific upper bound solutions are found using the method derived. The solutions are compared to an accurate slip-line solution and it is shown that the accuracy of the new method is very high.